The Effect Of Product, Price, Promotion and Place On Consumer Purchasing Decisions MBBAH Kitchen In Pontianak - Ari Maulana; Helman Fachri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of product variables, price, promotion, and location on consumer purchasing decisions. This study uses a quantitative approach and involves a population consisting of respondents who act as consultants MBBAH Kitchen in Pontianak. In this study, the number of samples used was 100 respondents. Data collection was conducted by providing questionnaires to respondents, then analyzed using the method of validity, reliability, normality. Hypothesis testing is done through simultaneous test (F test) and Partial Test (t test). The results showed that taken together, the variables of product, price, promotion, and location had a significant effect on consumers purchasing decisions. However, when partially analyzed, only products, promotions, and locations were shown to have a significant influence on purchasing decisions, while prices showed no significant influence.